2022
DOI: 10.1039/d2en00478j
|View full text |Cite
|
Sign up to set email alerts
|

Nanosilicon alters oxidative stress and defence reactions in plants: a meta-analysis, mechanism and perspective

Abstract: Alleviating the adverse effects of abiotic and biotic stress factors on crop plants is essential to achieve higher productivity for satisfying future food demands by the rapidly-growing global human population....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 67 publications
(118 reference statements)
1
25
0
Order By: Relevance
“…Along these lines, the mortality rate of rice weevil ( Sitophilus oryzae ) adults on rice plants treated with 1 g/kg hydrophilic nanosilica for 24 h was 9.5-fold higher than that with bulk silica . Therefore, in accordance with our hypothesis, Si NDs are better than bulk silica application for increasing plant resistance and growth (as shown above), but such effects are dose-dependent . The mechanisms related to these patterns are detailed below.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…Along these lines, the mortality rate of rice weevil ( Sitophilus oryzae ) adults on rice plants treated with 1 g/kg hydrophilic nanosilica for 24 h was 9.5-fold higher than that with bulk silica . Therefore, in accordance with our hypothesis, Si NDs are better than bulk silica application for increasing plant resistance and growth (as shown above), but such effects are dose-dependent . The mechanisms related to these patterns are detailed below.…”
Section: Resultssupporting
confidence: 76%
“…It has been shown that both bulk-Si and nano-Si could act as an exogenous stimulant of plants, which could induce a faster increase in JA especially under herbivore stress conditions. , However, our results suggest that soil application of Si NDs could promote the maize leaf to synthesize more phytohormones in response to herbivory than silicate addition. We can speculate that this effect might be related to the fact that Si ND treatment increased more soil silicic acids and leaf Si accumulation than silicate addition (Figure S3, Figure A), in turn promoting the effect of nanosilicon on JA production via activating plant defense-related gene expression. , …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations